2003
DOI: 10.1128/jcm.41.9.4270-4278.2003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Properties of Salmonella enterica Serotype Paratyphi B Distinguish between Its Systemic and Its Enteric Pathovars

Abstract: Salmonella enterica serotype O1,4,5,12:Hb:1,2, designated according to the current Kauffmann-White scheme as S. enterica serotype Paratyphi B, is a very diverse serotype with respect to its clinical and microbiological properties. PCR and blot techniques, which identify the presence, polymorphism, and expression of various effector protein genes, help to distinguish between strains with systemic and enteric outcomes of disease. All serotype Paratyphi B strains from systemic infections have been found to be som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 21 publications
2
61
2
Order By: Relevance
“…For example, in serovar Paratyphi B, strains from systemic infections always lack the avrA gene but contain sopE1, whereas strains from enteric infections generally display different absence-presence patterns for these genes (24). All systemic isolates investigated by Prager et al belonged to MLEE type 1 (Pb1).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in serovar Paratyphi B, strains from systemic infections always lack the avrA gene but contain sopE1, whereas strains from enteric infections generally display different absence-presence patterns for these genes (24). All systemic isolates investigated by Prager et al belonged to MLEE type 1 (Pb1).…”
Section: Discussionmentioning
confidence: 99%
“…Serovar Paratyphi B isolate S1583 was d-tartarate positive (indicative of biovar Java). This serovar normally causes nonsystemic disease symptoms (35), so it was surprising that there was considerable similarity to the serovar Typhi-encoded alleles of trpS, sseC, and sseF. Notably, there are extensive genetic differences within strains of serovar Paratyphi B (27,35,39), so the observation of a single strain with alleles similar to those of the human-adapted serovars might be possible.…”
Section: Discussionmentioning
confidence: 99%
“…This serovar normally causes nonsystemic disease symptoms (35), so it was surprising that there was considerable similarity to the serovar Typhi-encoded alleles of trpS, sseC, and sseF. Notably, there are extensive genetic differences within strains of serovar Paratyphi B (27,35,39), so the observation of a single strain with alleles similar to those of the human-adapted serovars might be possible. Otherwise, use of the island from STY4217 to STY4222 for molecular identification of human-adapted typhoidal serovars resolved the cross-reaction with strain S1583, as this region was not encoded in any serovar Paratyphi B isolate.…”
Section: Discussionmentioning
confidence: 99%
“…5-fold increase in invasive ability compared with the wildtype (Ehrbar et al, 2002), which may be sufficient to result in a small increase in transmissibility of sopE-positive strains and increase prevalence over time. Prager et al (2003) found that all isolates of S. Paratyphi B associated with systemic infection carried sopE, compared with only a small number of S. Paratyphi B associated with enteric infection. These strains are distinguished phenotypically only by their ability to utilize D-tartrate, but show markedly different levels of virulence in man.…”
Section: Sequence Analysis Of Sope Ampliconsmentioning
confidence: 99%